Searching for Excellence in Science Education: The African Experience - Ojimba, Daso Peter (Mediterranean Journal of Social Sciences, 2012)
This paper seeks to enumerate the search for excellence in Science Education, using the African experienceas its focal point. Science education in independent sub-Saharan Africa has been shaped by policies andpractices which owe allegiances to the colonial masters. All these nations strive to achieve scientific andtechnological knowledge. There is need to shift from the moribund, dogmatic and unimaginative curriculato alternatives that have definite and dynamic objectives based on the child as a potential citizen and askilled individual. Scientific knowledge has gone through several stages and revolutions from timeimmemorial up to these modern times. An understanding of the growth and changing nature of scientificideas helps to clarify some of the problems confronting Science education in modern times especially inAfrica. Scientific knowledge has increased both in quantity and in quality, so that old patterns of thoughthave been modified in ways that have caused profound changes in people’s views of natural phenomena.The search for excellence in Science education started with the desire for scientific literacy advocated by theuse of good Science education programmes in Africa. The aim was to ameliorate the unscientific cultureimbibed traditionally. Hence, the paper harped on education in Africa, objectives of education in Africa,objectives of science education in Africa, emergence of modern science education in Africa, attendantproblems of science education, and the need for relevant agencies to strive for excellence in scienceeducation in Africa.